Cerebral Blood Flow and Cognitive Functioning in a Community-Based, Multi-Ethnic Cohort: The SABRE Study - Leeuwis, Anna E.; Smith, Lorna A.; Melbourne, Andrew; Hughes, Alun D.; Richards, Marcus; Prins, Niels D.; Sokolska, Magdalena; Atkinson, David; Tillin, Therese; Jäger, Hans R.; Chaturvedi, Nish; Flier, Wiesje M. van der; et al. (Frontiers in Aging Neuroscience, 2018)
Abstract INTRODUCTION Lower cerebral blood flow (CBF) is associated with cardiovascular disease and vascular risk factors, and is increasingly acknowledged as an important contributor to cognitive decline and dementia. In this cross-sectional study, we examined the association between CBF and cognitive functioning in a community-based, multi-ethnic cohort. METHODS From the SABRE (Southall and Brent Revisited) study, we included 214 European, 151 South Asian and 87 African Caribbean participants (71±5yrs; 39%F). We used 3T pseudo-continuous arterial spin labelling to estimate whole-brain, hematocrit corrected CBF. We measured global cognition and three cognitive domains (memory, executive functioning/attention and language) with a neuropsychological test battery. Associations were investigated using linear regression analyses, adjusted for demographic variables, vascular risk factors and MRI measures. RESULTS Across groups, we found an association between higher CBF and better performance on executive functioning/attention (standardized ß [stß]=0.11, p<0.05). Stratification for ethnicity showed associations between higher CBF and better performance on memory and executive functioning/attention in the white European group (stß=0.14; p<0.05 and stß=0.18; p<0.01 respectively), associations were weaker in the South Asian and African Caribbean groups. CONCLUSIONS In a multi-ethnic community-based cohort we showed modest associations between CBF and cognitive functioning. In particular, we found an association between higher CBF and better performance on executive functioning/attention and memory in the white European group. The observations are consistent with the proposed role of cerebral hemodynamics in cognitive decline.